Manifestaciones orales en pacientes adultos diagnosticados con cáncer de cabeza y cuello bajo tratamiento oncológico. Revisión sistemática de la literatura (2023)
Head and neck cancer is a multifactorial disease that increasingly affects the population, therefore, it is essential, to know the oral, manifestations that may occur in the oral cavity due to treatments such as chemotherapy and radiotherapy in order to make timely diagnosis and management of these premalignant lesions.